Effect of annealing on the wear resistance of CrN/CrTiSiN PVD nitride coatings - Mohammadali Sohrabizadeh; Hassan Elmkhah; Meisam Nouri; Teng Fei Zhang (Journal of Materials Research and Technology)
Studying wear mechanisms is crucial in industry as wear significantly shortens the lifespan of equipment and components. This study investigated the effect of annealing temperatures on the wear mechanisms of CrN/CrTiSiN multilayer coatings. The coatings were annealed in air at temperatures ranging from 500 to 1000 °C for 1 h. XRD, SEM, FESEM, EDS, and ball-on-disk wear testing techniques were used. In the as-deposited and 500 °C annealed samples, the primary observed wear mechanism is plastic deformation, which results in the gradual detachment of particles (debris) from the substrate metal and the deformation of these particles along the wear path. Oxidative wear is characterized by fragmented debris and the retention of wear particles along the wear path. In contrast, annealing at temperatures between 700 °C and 1000 °C leads to the occurrence of oxidative wear, characterized by the oxidation of the metal surface and the abrasion of the oxides surface. The signs of oxidative wear include fragmented debris and the persistence of wear debris along the wear path, which are attributed to surface oxidation and the diffusion of oxygen into the coating. The factors influencing oxidative wear include increased surface oxides, debris fragmentation, and the retention of these particles along the wear path. This study recommends that CrN/CrTiSiN multilayer nanocomposite coatings should avoid exposure to operating temperatures exceeding 800 °C. To achieve optimal wear behavior, it is suggested to anneal the coating at 600 °C for 1 h in air atmosphere.